Vocational Identity in College Students: Path Analysis of Childhood Attachment, Gender, Age, and Socioeconomic Status - Strate, Lara; Michael, Tony; Hammond, Marie (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2023)
The purpose of this study was to explore the effect of gender, age, socioeconomic status, and early childhood parental attachment on vocational identity. Participants included 309 college students who completed a demographic questionnaire, the Adult Scale of Parental Attachment-Short Form (ASPA-SF; Michael & Snow, 2019), and My Vocational Situation (MVS; Holland, Gottfredson, & Power, 1980). Responses were examined through structural equation modeling. Results indicated an overall acceptable model fit and the specific strength of the corresponding variables had on the levels of vocational identity. Implications and areas for future research are proposed.